Teachers' and Students' Perceptions of the Role of Student Management in Strengthening Discipline: A Study at SMPQU - Devi Nurliana; Gina Muqti Fizih; Noor Robbiulliyah; Fatimah Az Zahro (UIN Siber Syekh Nurjati Cirebon, 2026)
Discipline is a fundamental aspect in the formation of student character that directly impacts academic success and personality. This study aims to describe and analyze in depth the perceptions of teachers and students regarding the role of student management in strengthening discipline at SMPIQu Al Bahjah Batam. This study used a qualitative approach with a case study design. Data were collected through in-depth interviews with the vice principal of student affairs, guidance counselors, homeroom teachers, and students with various levels of discipline. The results show that SMPIQU Al Bahjah implements student management through a planning, implementation, and evaluation process that integrates Islamic values and a points system for achievements and violations. The main findings revealed differences in perceptions between educators and students. Teachers view student management as a strategic instrument for developing character through role models and positive habits. Conversely, although most students accept rules as a means of education, there is a dynamic where students tend to view these policies as formal administrative restrictions that can limit their internal moral awareness. The implications of this research indicate the need for a transformation in student management strategies from a bureaucratic-structural approach to a more humanistic, persuasive, and participatory one. Involving students in regular evaluations of discipline is expected to increase their sense of ownership and align school policies with students' emotional acceptance, thus creating discipline based on genuine awareness.